Sustainable Dairy Farming: Harnessing Energy from Cattle Manure and Managing Wastewater Efficiently - AlSaab Darin H.; AlOtaibi Sarah E.; AlOtaibi Danah S.; AlSulaili Abdalrahman D. (E3S Web of Conferences, 2025)
Dairy farming in Kuwait faces significant environmental challenges, including high greenhouse gas emissions and inefficient manure management, necessitating sustainable alternatives. This study applies the Analytic Hierarchy Process (AHP) using SpiceLogic software to determine the most suitable manure management system for a 222,000 m² dairy farm in Sulaibiya housing 2,978 Holstein cows. Anaerobic digestion (AD) was identified as the optimal solution. Sixteen Continuous Stirred-Tank Reactor (CSTR) anaerobic digesters were designed to process 179.03 m³ of manure daily per unit, yielding 56,700.99 m³ of methane and generating 198.45 MWh of electricity. A greenhouse gas (GHG) emissions assessment was conducted using the European Economic Area (EEA) Grants method, revealing that electricity consumption from oil-fired power plants resulted in 1.77 million kg of CO2 emissions from 2016 to 2019 and 1.08 million kg from 2019 to 2021. Implementing AD reduced nitrous oxide emissions by 93.53%, from 2,525.5 to 163.5 metric tons CO2-equivalent, compared to the current drylot system. The digestate was identified as a bio-fertilizer, improving soil health and reducing chemical fertilizer reliance. A wastewater treatment plant (WWTP) was designed to treat 1,000 m³ of wastewater daily for irrigation reuse. Environmental impact assessments confirmed AD significantly reduces emissions compared to conventional manure management.